Setting Inventory Levels of CONWIP Flow Lines via Linear Programming - Stefan Helber; Katja Schimmelpfeng; Raik Stolletz (BuR - Business Research, 2011)
This paper treats the problem of setting the inventory level and optimizing the buffer allocation of closed-loop flow lines operating under the constant-work-in-process (CONWIP) protocol. We solve a very large but simple linear program that models an entire simulation run of a closed-loop flow line in discrete time to determine a production rate estimate of the system. This approach introduced in Helber, Schimmelpfeng, Stolletz, and Lagershausen (2011) for open flow lines with limited buffer capacities is extended to closed-loop CONWIP flow lines. Via this method, both the CONWIP level and the buffer allocation can be optimized simultaneously. The first part of a numerical study deals with the accuracy of the method. In the second part, we focus on the relationship between the CONWIP inventory level and the short-term profit. The accuracy of the method turns out to be best for such configurations that maximize production rate and/or short-term profit.
urn:nbn:de:0009-20-29798
Keywords: 650; CONWIP; flow lines; inventory; linear programming; Fließfertigung; Lagerhaltungsmodell; Mathematische Optimierung; Performance-Messung